Sistem Pakar Diagnosa Hipertensi Dengan Algoritma Naive Bayes - Azhar (Jurnal Elektro dan Informatika, 2021)
Many factors that affect public health such as smoking, rarely exercise, consume foods that contain lots of salt and so forth. So human blood becomes abnormal and can cause death. This high blood disease is suffered in pregnant women and adults over 30 years. This disease should be frequently consulted by a doctor to be able to cope with sudden blood ascending from normal blood. So people who suffer from this disease should be more often in checking high blood presure based on the above problems then built a system of expert diagnosis of hypertensive disease that can diagnose early to overcome the disease. Expert system method used is naive bayes. This system is built to overcome certainty and uncertain on the intensity of different symptoms - different on each disease, so users can know the type of disease suffered by the user and treatment to overcome the disease. Based on the calculation, obtained the percentage of disease success in the expert system that is equal to 84.61% and the unsuccessful of 15.38% of the 13 data that have been tested on the expert system.